2013
DOI: 10.1142/s0219887813600104
|View full text |Cite
|
Sign up to set email alerts
|

T-Duality Invariance of the Supermembrane

Abstract: We show that the supermembrane theory compactified on a torus is invariant under Tduality. There are two different topological sectors of the compactified supermembrane (M2) classified according to a vanishing or nonvanishing second cohomology class. We find the explicit T-duality transformation that acts locally on the supermembrane theory and we show that it is an exact symmetry of the theory. We give a global interpretation of the T-duality in terms of bundles. It has a natural description in terms of the c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Let us recall [20,57], the relation between the radius modulus and its dual follows from (22), was obtained in:…”
Section: B 'T-duality' Action On the Mass Operatormentioning
confidence: 99%
See 2 more Smart Citations
“…Let us recall [20,57], the relation between the radius modulus and its dual follows from (22), was obtained in:…”
Section: B 'T-duality' Action On the Mass Operatormentioning
confidence: 99%
“…with H = H. See [20] for further details. In [57] the authors showed that there always exists a T a parabolic matrix transformation of 'T-duality' given for any arbitrary value of the KK and winding charges. This parabolic transformation depends on the winding and KK momenta of the supermembrane bundle.…”
Section: B 'T-duality' Action On the Mass Operatormentioning
confidence: 99%
See 1 more Smart Citation
“…The gauging of the R + scaling symmetry called trombone gives supergravities without lagrangians [29,30]. At quantum level this last symmetry corresponds to an SL(2, Z) non linearly realized and gives rise to a different symplectic torus bundle in comparison to the previous constructions in terms of linear representations [12,13]. Indeed, only when the monodromy is parabolic, the T-duality action is linear meanwhile for the elliptic and hyperbolic case, T-duality does not commute with the monodromy but forms a unique class of torus bundles in the type IIA side with an scaling symmetry A(1).…”
Section: Supermembrane Theory and Gauged Supergravity In 9dmentioning
confidence: 99%
“…The supermembrane without the central charge condition corresponds to the type II maximal supergravity in nine dimensions. The mass operator and the hamiltonian are U-dual invariant [11] and when supermembrane is dimensionally reduced to string theory T-duality for supermembranes agree with the standard one in string theory compactified on a circle [13]. Moreover, for the supermembrane with nontrivial central charge, it was found all the inequivalent classes of torus bundles with SL(2, Z) monodromy that describes globally the theory, [12].…”
Section: Introductionmentioning
confidence: 98%